Effective virtual laboratory to build constructivist thinking in electrical measurement practicum - Fivia Eliza; Oriza Candra; Doni Tri Putra Yanto; Radinal Fadli; Dwiprima Elvanny Myori; Syaiful Islami; Yayuk Hidayah; Levandra Balti (Indonesian Journal of Electrical Engineering and Computer Science, 2024)
Constructivism serves as a basic theory in education, and plays an important role, because this perspective views learning as a dynamic process in which students actively participate in constructing their knowledge. So, this research aims to produce a virtual laboratory that is valid and effective in developing constructivist thinking. This research and development use the Ploom approach which consists of initial investigation, design, construction/realization, testing, evaluation, revision, and implementation. Thirty-two electrical engineering students from Padang State University participated in this research. The instruments used are validity instruments and constructivism assessment tools. The research results show that the Proteus-based virtual laboratory developed is valid and effective in fostering constructivist thinking in electrical measurement practice. This study contributes to the advancement of virtual laboratories in educational settings, emphasizing the importance of constructivist pedagogy for meaningful and engaging learning experiences in the field of electrical engineering. The results of this research open opportunities for further research regarding the exploration of artificial intelligence to improve constructivism through virtual laboratories.